2007
DOI: 10.1017/s0030605307001639
|View full text |Cite
|
Sign up to set email alerts
|

The decline of the endemic Fijian crested iguana Brachylophus vitiensis in the Yasawa and Mamanuca archipelagos, western Fiji

Abstract: The endemic Fijian crested iguana Brachylophus vitiensis, categorized as Critically Endangered on the IUCN Red List, has been recorded from several islands in western Fiji. We conducted a survey for the crested iguana on 12 uninhabited and five inhabited islands in the Yasawa and Mamanuca archipelagos of western Fiji in September 2000. Night searches for sleeping iguanas along a total of 11.2 km of forest transects suggest that crested iguanas are either extremely rare or extinct on all of these islands. Altho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
20
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 4 publications
2
20
0
Order By: Relevance
“…Although we have some knowledge of the habitat and vegetation preferences of B. vitiensis, this work has been largely opportunistic in nature (with the exception of Harlow and Biciloa [2001] and Harlow et al [2007]). A previous study of B. vitiensis on Yadua Taba demonstrated that iguanas were primarily found in forest vegetation, were not found in nonnative forest types including grasslands, and were observed in very low abundance in rocky-cliff or shrubland vegetation (Harlow and Biciloa 2001).…”
Section: Critically Endangered Fijian Crested Iguana (Brachylophus VImentioning
confidence: 99%
See 4 more Smart Citations
“…Although we have some knowledge of the habitat and vegetation preferences of B. vitiensis, this work has been largely opportunistic in nature (with the exception of Harlow and Biciloa [2001] and Harlow et al [2007]). A previous study of B. vitiensis on Yadua Taba demonstrated that iguanas were primarily found in forest vegetation, were not found in nonnative forest types including grasslands, and were observed in very low abundance in rocky-cliff or shrubland vegetation (Harlow and Biciloa 2001).…”
Section: Critically Endangered Fijian Crested Iguana (Brachylophus VImentioning
confidence: 99%
“…Previous published estimates of the population size of iguanas on Yadua Taba range from 200 (Gibbons 1981) to over 6,000 (Laurie et al 1987, Harlow andBiciloa 2001) and also report higher abundances in tropical dry forest and coastal tropical dry forest. Few (3%) iguanas were found in Casuarina forest with tropical dry forest un-dergrowth, suggesting that a closed canopy, which Casuarina does not provide, may be important for iguanas to avoid predation by Pacific harriers (Circus approximans) (Harlow et al 2007).…”
Section: Forest Regenerationmentioning
confidence: 99%
See 3 more Smart Citations